Evaluating the bacterial culture technique by Polymerase chain reaction for the diagnosis of Brucella abortus in milk of cows suspected with brucellosis.: Bashar Sadeq Noomy and Nihad Abdulhassan Jafar - Noomy, Bashar Sadeq (The Iraqi Journal of Veterinary Medicine, 2016)
The aim of this study is to determine the sensitivity of bacterial culture technique in the detection of Brucella abortus in milk samples of aborted cows. Sixty samples of milk were collected from aborted cows during a period which did not exceed two months after the abortion. All of them were positive for rose bengal test. Results showed that Brucella abortus was isolated from 7 out of 60 (11.6%) from the milk of aborted cows, while PCR test showed that 32 out of 60 (53.3%) milk sample contained Brucella abortus. The specificity of culture techniques was 10%, but its sensitivity was only 21.8%. Beside the cautions in dealing with live Brucella abortus (as culture), it is also less sensitive than PCR, though it is better to use PCR technique in the diagnosis of brucellosis in aborted cows milk.